Penyuluhan Kelompok Petani dalam Budidaya dan Pengolahan Ikan Lele dengan Cara Pemberian Bumbu Alami di Kabupaten Banyuasin - Selly Ratna Sari; Elmeizy Arafah; Guttifera Guttifera; Rizki Eka Puteri; Raudhatus Sa'adah (Penerbit Goodwood, 2022)
Purpose: The community service activities to provide knowledge about aquaculture as well as recommendations for consuming processed fish, increasing community income in river village two and hope to provide understanded to the community who participate in activities, especially in the field of fisheries. Methodology/approach: The activities of community were at the outdoor laboratory ini Sungai Dua village of the University South Sumatra. The activities community purposed at advised to consumption of processed fish product, increasing the income of the community-specific community in Sungai Dua village and hope so to provide understanding to the people who follow community service activities.The activity went smoothly attended by approximately 100 participants in the Laboratory outdoor of fisheries science study program. Results/findings: The advantage of this training is that the people in Sungai Dua Village know all activities from catfish aquaculture to processing fishery products so that people have motivation in entrepreneurship, business alternatives and fond of eating fish. Conclusion: The community service activities on of processed catfish in Sungai Dua village are joined by the people of Sungai Dua village. Activities include the presentation of like to eat fish, shared of leaflets and shared about aquaculture until of processed fish product.. The participants were enthusiastic. People who follow the training have more motivation to need to be of fisheries.